Exploring Continuous Assessment in Private Schools of Kathmandu Valley: A Teachers’ Perspectives - Dhungel, Pratigya (NPRC Journal of Multidisciplinary Research, 2024)
This study titled “Exploring Continuous Assessment in Private Schools of Kathmandu Valley: A Teachers’ Perspectives” explores the implementation of continuous assessment systems aiming to shed light on the context, problems, and rationale for investigating continuous assessment practices in private schools of Kathmandu Valley through narrative inquiry. It highlights the significance of the study in addressing the limitations of traditional assessment methods. My personal experience as a student serves as a backdrop to the research, emphasizing the impact of memorization-based assessments on individual learning experiences. The literature review section of the study encompasses a thematic review of continuous assessment, different approaches to assessments, assessment practices in Nepal, and a theoretical review of constructivism. I have drawn on constructivist perspectives to explore the relationship between continuous assessment and learning goals, emphasizing the importance of aligning assessment with the active construction of knowledge. The study's findings reveal insights into the challenges posed by traditional assessment methods, the readiness for change, and the potential benefits of continuous assessment systems. The research also discusses the implications of continuous assessment practices for educators and policymakers, highlighting the need for intervention and reform in the education sector.